2010
DOI: 10.1038/labinvest.2009.138
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of FBXO32, a novel TGF-β/SMAD4 target gene and tumor suppressor, is associated with poor prognosis in human ovarian cancer

Abstract: Resistance to TGF-b is frequently observed in ovarian cancer, and disrupted TGF-b/SMAD4 signaling results in the aberrant expression of downstream target genes in the disease. Our previous study showed that ADAM19, a SMAD4 target gene, is downregulated through epigenetic mechanisms in ovarian cancer with aberrant TGF-b/SMAD4 signaling. In this study, we investigated the mechanism of downregulation of FBXO32, another SMAD4 target gene, and the clinical significance of the loss of FBXO32 expression in ovarian ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 35 publications
5
92
0
Order By: Relevance
“…Moreover, patients with higher FBXO32 promoter methylation tend to have shorter progression-free survival. This suggests a tumor-suppressive role of FBXO32 (9). In addition, the FBXO32 expression is also decreased in esophageal squamous cell carcinoma (10).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, patients with higher FBXO32 promoter methylation tend to have shorter progression-free survival. This suggests a tumor-suppressive role of FBXO32 (9). In addition, the FBXO32 expression is also decreased in esophageal squamous cell carcinoma (10).…”
mentioning
confidence: 84%
“…The expression level of FBXO32 is closely correlated with the methylation status of the FBXO32 promoter in ovarian cancer cell lines (9). Restoration of FBXO32 in ovarian cancer cells inhibits colony formation in vitro and xenograft tumor growth in athymic nude mice.…”
mentioning
confidence: 98%
“…Interestingly, Tan and colleagues also showed that FBXO32 was transcriptionally silenced by epigenetic mechanisms in cancer cells (48). Furthermore, Chou and colleagues found that FBXO32 might be a novel tumor suppressor gene that was associated with poor prognosis in human ovarian cancer (50). Our reporter gene assays suggested that the rs4919510C allele affected FBXO32 expression by inhibiting the binding of miR-608 in nasopharyngeal carcinoma cell lines, and these results are consistent with previous findings on the contributions of FBXO32 to tumor suppression.…”
Section: Cne-2-empty Vectormentioning
confidence: 99%
“…As shown in Table IV (10,11,14,16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(29)(30)(31)(32)(33)(34)(35)(36)38,39,(41)(42)(43)(44)(45)(47)(48)(49)(50)(51)(52), we observed that a considerable number of DNA methylated genes, including MLH1, FBXO32, PROM1, RASSF1, PTEN, SFRP, TUBB3, L1TD1 and CLDN4, were associated with the invasion of ovarian cancer. Each gene was hypermethylated, resulting in the silencing of gene expression in ovarian cancer and drug-resistant tissue or cells and ultimately regulating tumour invasion.…”
Section: Correlation Analysis Of Ovarian Cancer Drug Resistance-relatmentioning
confidence: 54%